Perfil clínico e laboratorial dos pacientes com leucemia linfoide crônica atendidos no serviço de hematologia e hemoterapia do HUWC-HEMOCE - Custódio, Richeyla Kelly de Assis (2009)
Chronic Lymphocytic Leukemia (CLL) is the most frequent leukemia on western countries, responding for 30% off all leukemia cases, reaching, specially, the under 65 years old population. It is characterized by accumulation of neoplasic mature B lymphocytes positives CD5. Concerning epidemiology, it is barely seen among eastern people, and its incidence is not influenced by environmental agents, such as toxic substances or ionizing radiation. CLL-B patients may present a variable clinical evolution, which goes from indolent to aggressive and rapidly fast cases. On last decade, there have been great advance on biology knowledge of this disease, and greater impact prognostic factors have been established. In relation to treatment, new medication, with better efficacy, appeared. Therefore, it is interesting to know the real situation of this disease, which has singular epidemiological, clinical and prognostic characteristics. In this work we trace the demographical, clinical and laboratorial profile of patients with CLL-B, at a state hemocenter (HEMOCE). We correlate prognostic markers expression (CD38 e ZAP-70) with some variable and with pharmacological treatment. We used 55 blood samples from patients CLL-B confirmed by their immunophenotypes; these patients may or may not be in treatment. CD38 and ZAP-70 were analyzed by flow cytometry and β2-microglobulin dosage, obtained through ELISA. Results were treated by statistic program. We see a discrete prevalence of male patients (1,4:1), 78% are under 65 years old and 60% live at Ceará’s capital. In relation to Rai staging system, 50,9% were classified as low risk patients. Concerning clinical evolution, more than 30% of the patients did not show clinical signs, neither at diagnose moment nor at the end of this study. In relation to the markers, 22,2% of the patients show ZAP-70 expression, and 24,13% show CD38 expression. There was no significant statistic difference between ZAP-70 and CD38 markers and hematological variable (Hb, Ht and platelets). There was correlation between Rai’s staging and pharmacological treatment and with prognostic markers. CONCLUSION: The profile was characterized by low risk patients, according Rai’s staging, it lacks prognostic markers expression and it also lacks specific treatment.